Performance studies on proton exchange membrane fuel cell with slightly tapered single flow channel for dissimilar cell potentials. (2023) - Girimurugan, R.; Anandhu, K.; Thirumoorthy, A.; Harikrishna, N.; Makeshwaran, E.; Prasanna, S.; Krishnaraj, R.
Abstract: For a PEMFC, the geometrical and operational variables are critical to its performance. The fuel cell's active surface is uniformly supplied with reactants thanks to the flow channels. Numerical results are presented here for a PEMFC single flow channel with a little taper at various cell voltages (0.2 V to 0.9 V). Straight flow channel and three slightly tapered (0.25 mm, 0.5 mm and 0.75 mm) single flow channel PEM fuel cells were built using a commercial modelling tool and studied using the COMSOL Multiphysics software package, which is used to model and simulate complex physical systems. Taper settings and cell potentials were varied to maximize PEMFC effectiveness. Taper flow channel PEMFCs at a voltage of 0.35 V exhibit indications of superior performance compared to straight flow channel PEMFCs. Performance and polarization curves were drawn from the numerical results. The current densities, power densities, anode Hydrogen concentration, cathode Oxygen concentration, anode water concentration, cathode water concentration of straight and three different slightly tapered flow channels of PEMFC with fifteen different cell potentials were compared with each other. The maximum current and power densities of 2.34936 A/cm 2 and 0.59310 W/cm 2 for the cell potential of 0.35 V for 0.25 mm taper flow channel PEM fuel cell configuration.